Network marketing- reality, myth, dream or a success mechanism: a review - Jyoti, Jiwan (Journal of Management and Science, 2013)
As the Business Enviornment become more and more competetive, companies are forced to push themselves to very edge of their capabilities. Ultimately the success of companies relies on their human resources and business and marketing strategies wich can help them to show up in global markets. So Network Marketing has become increasingly used method in order to ehance the small and large logistic companies performance. Multi-level marketing is a marketing approach that motivates its participants to promote a certain product among their friends. The popularity of this approach increases due to the accessibility of modern social networks, however, it existed in one form or the other long before the Internet age began (the infamous Pyramid scheme that dates back at least a century is in fact a special case of multi-level marketing). The India Direct Selling Association (IDSA) has projected that the network marketing industry will be around Rs 9000 crores by 2013 end.The purpose of this paper is to provide better understanding of how Network Marketing is used as Marketing strategy and tool to develop logistic companies business in new millennium. The idea is to seek roots in localised practices in rapidly unfolding globalisation and thus paving the way for ―globalisation‖.